Analisis Proses Penanganan Bagasi Tertinggal Maskapai Fly Scoot di Bandara Internasional ZAM Lombok - Melani Devita Sari Putri; Andityo Pujo Laksono (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the handling of left-behind baggage by Lost & Found officers of PT Gapura Angkasa for Fly Scoot airline at Zainnudin Abdul Madjid Internation Airport, Lombok. Left -behind baggage is a critical issue in ground handling service as it directly affects passenger satisfaction and the airline’s reputation. This research employs a descriptive qualitative method, using data collection techniques such as observation, interviews, and documentation. The findings reveal several key factors contributing to babbage being left-behind, including limited time during connecting flights, labeling errors, and the inclusion of prohibited items such as betteries and power bank is cheked baggage. Additionally, procedural errors and human error were also identified as challenges in the handling process. To address these issues, Lost & Found Officers track baggage through the World Tracer system, coordinate with the origin airport and related airline, and arrange delivery of the baggage to passengers’ addresses. This research is expected to serve as an evaluative reference for improving the quality of left-behind baggage handling services at the airport.